(untitled) (مجلة إحالات, 2026)
In the modern era, one of topic that was widely talked about is captivity. It was covered by several foreign scholars who either observed or were involved with the phenomena, that was so widespread because of the conjuncture of the time. As an example, Miguel de Cervantes who were a prisoner in the capital of the turkish Regency for five years and its vicissitudes, aimed at fleeing the suffering. We will discuss throughout our analysis of the third part of this autobiographical literary work known as « peddling », what were the conditions of the captivity of the author himself and the secrets of the society of yesteryear.